CYSTACANTHS OF GIGANTORHYNCHUS ECHINODISCUS (ACANTHOCEPHALA, GIGANTORHYNCHIDAE), IN NEOTROPICAL TERMITES (ISOPTERA, TERMITIDAE) - R. Amato, José F. (2014)
Specimens of Labiotermes emersoni (Araujo, 1954) and Orthognathotermes heberi Raw & Egler, 1985, were collected at Parque Nacional da Serra da Canastra, State of Minas Gerais, Brazil. Soldiers of the two species were suspected to carry larval acanthocephalan parasites due to different sizes and shape of their heads and because some specimens had a conspicuous, cylindrical, whitish 'body' in the hemocoel, around the digestive tract in the abdomen. The termites showed shape alteration and light pigmentation dystrophy of the heads induced by the larval acanthocephalans. These alterations were documented photographically and the cystacanths described. The encysted juveniles removed from the hemocoel of infected soldier termites and processed accordingly, were determined as Gigantorhynchus echinodiscus (Diesing, 1851). The proboscis had the typical cylindrical shape and the characteristic two distal circles of large hooks (6+12), covered with small, almost rootless spines, and a very short neck. This is the first record from Brazil of any species of termites infected with acanthocephalans of the genus Gigantorhynchus Hamann, 1892 and the first record of G. echinodiscus cystacanths infecting the intermediate host.